Stories of witches - Harvey, Gill; Cartwright, Stephen Kelly, Alison Rawson, Christopher (Usborne London, 2007)
Four original stories about witches for children just beginning to read. Featuring wicked, wily witches, these stories are guaranteed to delight children while developing their reading ability. Usborne Young Reading has been developed with reading experts from Roehampton University.